Teologie as werklikheidsverstaan – anders dink, anders doen: Aantekeninge oor die teologie van Johan Buitendag - Aarde, Andries van (HTS teologiese studies, 2014)
Theology as understanding reality – thinking differently, acting differently: Notes about the theology of Johan Buitendag. The article investigates the theological contours delineated from the publications of the systematic theologian Johan Buitendag. His theology represents a relational integrity of ontology, epistemology and ethics. It can be characterised as an existential ecotheology. In the introduction this rhizome (epistemological metaphor borrowed from Giles Deleuze and Félix Guattari) existence in Buitendag’s theology is discussed. The article consists of nine sections: the hermeneutical circle as introduction; the polemic attitude of Karl Barth with regard to a theologia naturalis; understanding the notion paradigm; being church as a relational event; engaged epistemology; existential theo-anthropology and ecotheology; existential ecclesiology; existential engagement; and an autobiographical reflection.